Pengembangan Bahan Ajar Elektronik Berbasis Canva pada Materi Kubus dan Balok dengan Pendekatan PMRI Berorientasi Konteks Islam Melayu - R. Evenda Ceria; Muhammad Win Afgani; Retni Paradesa (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
The advancement of technology in education necessitates facilitators in the form of teachers who design creative teaching materials and are oriented toward technology-dominant education. The purpose of this study is to produce canva-based electronic teaching materials on cube and beam materials with a PMRI approach oriented to the Malay Islamic context that is valid, practical, and has potential effects. The developed electronic teaching material is e-modules. This type of research is called development research, which uses the Tessmer formative research model. The research process consists of two stages, namely the first, preliminary, which includes the preparation and design stages, and the second, formative evaluation, which includes the self-evaluation, expert review, one-to-one, small group, and field test stages. The presentation in the e-module teaching materials is prepared using the PMRI approach and is associated with the Malay Islamic context. The e-module teaching materials were tested on class IX MTs Fajar Siddiq students. This research obtained the result that the development of teaching materials in the form of e-modules was declared valid and practical through qualitative analysis. The validity of teaching materials is obtained at the expert review stage through validator comments and suggestions. Practicality is obtained at the one-to-one and small group stages through the analysis of student comments and suggestions. Potential effects are obtained from student evaluation tests at the field test stage. The developed e-module teaching materials have a potential effect with a percentage of completion of 81.8% on problem solving.